Identification of two mismatch-binding activities in protein extracts of Schizosaccharomyces pombe. - Fleck, O (1994)
We have performed band-shift assays to identify mismatch-binding proteins in cell extracts of Schizosaccharomyces pombe. By testing heteroduplex DNA containing either a T/G or a C/C mismatch, two distinct band shifts were produced in the gels. A low mobility complex was observed with the T/G substrate, while a high mobility complex was present with C/C. Further analysis of the mismatch-binding specificities revealed that the T/G binding activity also binds to T/C, C/T, T/T, T/-, A/-, C/-, G/-, G/G, A/A, A/C, A/G, G/T, G/A, and C/A substrates with varying efficiencies, but not binds to C/C. The C/C binding activity efficiently binds to C/C, T/C, C/T, C/A, A/C, C/-, and weakly also to T/T, while all other mispairs are not recognized. Protein extracts of a mutant strain, defective in the mutS homologue swi4, displayed both mismatch-binding activities. Thus, swi4 does not encode for either one of the mismatch-binding proteins.